Pengaruh harga CPO, harga minyak mentah dunia, harga karet dunia dan kurs terhadap defisit neraca transaksi berjalan Indonesia - Bondan Noviantoro; Emilia Emilia; Yohanes Vyn Amzar (Jurnal Paradigma Ekonomika, 2017)
Current account balance is a measuring instrument about Indonesian international trade, but current account balance tends to be unbalanced. This resource conducted to analyze influence of CPO price, world crude oil price, world rubber price, and exchange rate to Indonesian current account deficit. The Data which used is secondary data and sourced from World Bank and Indonesian Bank that have year period 2010Q1-2015Q4. Analytical tool that used is multiple linear regression analysis. Based on the result of the research that variable price of CPO, world crude oil price, world rubber price, and exchange rate jointly significant effect to Indonesian current account deficit. Determination coefficient value of 0,716 which means the effect of variations in changes in independent variables to the dependent variable is equal to 71,60% and is affected by the outside research variables. Statistic result t shows variable price of CPO and exchange rate partially significant effect while world crude oil price and world rubber price do not partially significant effect.